2010
DOI: 10.1121/1.3478785
|View full text |Cite
|
Sign up to set email alerts
|

Musical intervals and relative pitch: Frequency resolution, not interval resolution, is special

Abstract: Pitch intervals are central to most musical systems, which utilize pitch at the expense of other acoustic dimensions. It seemed plausible that pitch might uniquely permit precise perception of the interval separating two sounds, as this could help explain its importance in music. To explore this notion, a simple discrimination task was used to measure the precision of interval perception for the auditory dimensions of pitch, brightness, and loudness. Interval thresholds were then expressed in units of just-not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 76 publications
(61 reference statements)
18
61
1
Order By: Relevance
“…Prior discourse studies have suggested that the highest pitch extrema-which the authors designated the e-la-may be associated with linguistic evaluative devices. In fact, the discourse intonation limen for discrimination was identified by 't Hart (1981) and is in line with recent Just Noticeable Difference (JND) data revealed by a "dual pair discrimination experiment" reported by McDermott et al (2010). The JND extracted from figures in the latter work are, respectively, 317¢ 6 95¢ for non-musicians and 217¢ 6 167¢ for musicians for the limen for the discrimination of which two pair of tones are perceived as the same pitch while the other pair are perceived as different.…”
Section: Distribution Fitting Modelssupporting
confidence: 86%
See 1 more Smart Citation
“…Prior discourse studies have suggested that the highest pitch extrema-which the authors designated the e-la-may be associated with linguistic evaluative devices. In fact, the discourse intonation limen for discrimination was identified by 't Hart (1981) and is in line with recent Just Noticeable Difference (JND) data revealed by a "dual pair discrimination experiment" reported by McDermott et al (2010). The JND extracted from figures in the latter work are, respectively, 317¢ 6 95¢ for non-musicians and 217¢ 6 167¢ for musicians for the limen for the discrimination of which two pair of tones are perceived as the same pitch while the other pair are perceived as different.…”
Section: Distribution Fitting Modelssupporting
confidence: 86%
“…The estimated uncertainty in the peak positions ranged from a low of approximately 1¢ to a maximum of 120¢ for a very broad and poorly resolved peak of low population, with the root-mean-square standard error for the combination of all peak determinations of approximately 27¢. This value is just below the threshold of discrimination for the untrained ear (McDermott et al, 2010).…”
Section: Estimated Error In Pitch Determinationmentioning
confidence: 96%
“…Rakowski (1990) found that the standard deviation of the production results for a certain interval was correlated with the percentage of errors in recognizing that interval. Ranking thresholds have been measured for only ascending intervals using the method of constant stimuli (e.g., Burns and Ward, 1978;Burns and Campbell, 1994;Zarate et al, 2012) or adaptive procedures (Burns and Ward, 1978;McDermott et al, 2010). On average, ascending interval ranking thresholds were below 1 semitone (i.e., the smallest tonal unit in Western music) for musicians, but above 1 semitone for non-musicians.…”
Section: Introductionmentioning
confidence: 99%
“…see (Foster and Zatorre 2010;McDermott et al 2010)), especially if contour violations and tonal melodies are excluded (Dowling 1986). McDermott et al (2010), commenting on the poor pitch interval discrimination threshold they found, suggested that the importance of pitch as an expressive musical feature may rest more on an ability to detect pitch differences between tones, rather than an ability to recognise complex patterns of pitch intervals.…”
Section: Introductionmentioning
confidence: 99%